Tracking gender equity under economic reforms : continuity and change in South Asia - Mukhopadhyay, Swapna; Sudarshan, Ratna M. (International Development Research Centre ; Kali for Women, 2003)
Contributed articles on women employees in economic development process in South Asia. By expanding the existing set of indicators to include gender-related stress, anxiety, and violence, this book introduces a new framework for gender research. The viability of this new approach is demonstrated through a coordinated set of household surveys, carried out in Export Processing Zones and Export Processing Units, designed for intercountry comparisons between Bangladesh, India, Pakistan, and Sri Lanka. This book is unique in its examination of both “conventional” and “nonconventional” indicators of gender disparity, and in its attempts to see how both may be affected by changes in macroeconomic policy. While “conventional” indicators include such variables as education, employment, and health status, on which official data are usually available, very little information is available on “nonconventional” indicators, such as levels of gender-based mental stress and violence. Also, instead of focusing on one aspect or indicator alone, this book takes a holistic look at a set of indicators, identifying common patterns and insights.